17‐Beta Hydroxysteroid Dehydrogenase 13 Deficiency Does Not Protect Mice From Obesogenic Diet Injury. Issue 5 (16th March 2021) - Ma, Yanling; Brown, Philip M.; Lin, Dennis D.; Ma, Jing; Feng, Dechun; Belyaeva, Olga V.; Podszun, Maren C.; Roszik, Jason; Allen, Joselyn N.; Umarova, Regina; Kleiner, David E.; Kedishvili, Natalia Y.; et al.
Abstract : Background and Aims: 17‐Beta hydroxysteroid dehydrogenase 13 (HSD17B13) is genetically associated with human nonalcoholic fatty liver disease (NAFLD). Inactivating mutations in HSD17B13 protect humans from NAFLD‐associated and alcohol‐associated liver injury, fibrosis, cirrhosis, and hepatocellular carcinoma, leading to clinical trials of anti‐HSD17B13 therapeutic agents in humans. We aimed to study the in vivo function of HSD17B13 using a mouse model. Approach and Results: Single‐cell RNA‐sequencing and quantitative RT‐PCR data revealed that hepatocytes are the main HSD17B13‐expressing cells in mice and humans. We compared Hsd17b13 whole‐body knockout (KO) mice and wild‐type (WT) littermate controls fed regular chow (RC), a high‐fat diet (HFD), a Western diet (WD), or the National Institute on Alcohol Abuse and Alcoholism model of alcohol exposure. HFD and WD induced significant weight gain, hepatic steatosis, and inflammation. However, there was no difference between genotypes with regard to body weight, liver weight, hepatic triglycerides (TG), histological inflammatory scores, expression of inflammation‐related and fibrosis‐related genes, and hepatic retinoid levels. Compared to WT, KO mice on the HFD had hepatic enrichment of most cholesterol esters, monoglycerides, and certain sphingolipid species. Extended feeding with the WD for 10 months led to extensive liver injury, fibrosis, and hepatocellular carcinoma, with no difference between genotypes. Under alcohol exposure, KO and WT mice showed similar hepatic TG and liver enzyme levels. Interestingly, chow‐fed KO mice showed significantly higher body and liver weights compared to WT mice, while KO mice on obesogenic diets had a shift toward larger lipid droplets. Conclusions: Extensive evaluation of Hsd17b13 deficiency in mice under several fatty liver–inducing dietary conditions did not reproduce the protective role of HSD17B13 loss‐of‐function mutants in human NAFLD. Moreover, mouse Hsd17b13 deficiency induces weight gain under RC. It is crucial to understand interspecies differences prior to leveraging HSD17B13 therapies.